Disruption in Brain Phospholipid Content in a Humanized Tau Transgenic Model Following Repetitive Mild Traumatic Brain Injury - Ojo, Joseph O.; Algamal, Moustafa; Leary, Paige; Abdullah, Laila; Mouzon, Benoit; Evans, James E.; Mullan, Michael; Crawford, Fiona (Frontiers in Neuroscience, 2018)
Repetitive mild traumatic brain injury (mTBI) is a risk factor for the development of neurodegenerative diseases such as chronic traumatic encephalopathy typified by immunoreactive tau aggregates in the depths of the sulci. However, the underlying neurobiological mechanisms involved have not been largely explored. Phospholipids are important molecules which form membrane lipid bilayers; they are ubiquitous to every cell in the brain, and carry out a host of different functions. Imbalance in phospholipid metabolism, signaling and transport has been documented in some neurological conditions. However, not much is currently known about their roles in repetitive mTBI and how this may confer risk for the development of age-related neurodegenerative diseases. To address this question, we designed a longitudinal study (24hr, 3, 6, 9, 12 months post-injury) to comprehensively investigate mTBI dependent brain phospholipid profiles compared to sham counterparts. We use our established mouse model of repetitive mTBI that has been extensively characterized up to one-year post-injury in humanized tau (hTau) mice, which expresses all six human tau isoforms, on a null murine background. Our data indicates a significant increase in sphingomyelin, phosphatidylethanolamine (PE), phosphatidylcholine (PC), and derivative lysoPE and lysoPC at acute and/or sub-acute time points post-injury within the cortex and hippocampus. There was also a parallel increase at early time points in monounsaturated, polyunsaturated and saturated fatty acids. Omega-6 (arachidonic acid) to omega-3 (docosahexaenoic acid) fatty acid ratio for PE and PC species was increased also at 24hrs and 3 months post-injury in both hippocampus and cortex. The long-term consequences of these early changes in phospholipids on neuronal and non-neuronal cell function is unclear, and warrants further study. Understanding phospholipid metabolism, signaling and transport following TBI could be valuable; they may offer novel targets for therapeutic intervention not only in TBI but other neurodegenerative diseases.